If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 13(2x + -4) = -20 Reorder the terms: 10 + 13(-4 + 2x) = -20 10 + (-4 * 13 + 2x * 13) = -20 10 + (-52 + 26x) = -20 Combine like terms: 10 + -52 = -42 -42 + 26x = -20 Solving -42 + 26x = -20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + 26x = -20 + 42 Combine like terms: -42 + 42 = 0 0 + 26x = -20 + 42 26x = -20 + 42 Combine like terms: -20 + 42 = 22 26x = 22 Divide each side by '26'. x = 0.8461538462 Simplifying x = 0.8461538462
| 3+x=11 | | lny=ln(x)+ln(C) | | 7x+28=27x+2 | | 36x^2-169y^2= | | p-36=-48 | | x^2+3x^2=40 | | -2x-7=13x-5 | | 7-6[9-(4y-3)]= | | 4x+36=12x-32 | | (4x+4)*(7x-3)= | | (4x+4)(7x-3)= | | 18x+16=60 | | 3x=7x-12-5x | | 2(4+x)=18 | | 15x+4*4=18x*3 | | 15x+4*4=3*18x | | -2x-9-4x=9x+21 | | 6(3+4x)=282 | | 5x^2-23x-42=0 | | 15x+4*x=21 | | y^3+10y^2+24y=0 | | x+4+3x=12 | | 2y+6=y+10 | | y^2-9y=-14 | | 2n-7+3n=18 | | 2x+6+6x=86 | | t^2-2t=20 | | 27x^2-18x+3=0 | | 10x^2+72x-64=0 | | 102-(4x+15)=4(x+6)+x | | y^2(y-4)=5y-14 | | 48-16= |